APPLICATION OF QUICK ON THE DRAW MODEL TO IMPROVE EXPOSITORY WRITING SKILLS FOR FIFTH GRADE STUDENTS OF SDN 2 KARANGPOH IN ACADEMIC YEAR OF 2020/2021 - Rifqi Aulia Rahman; Suhartono Suhartono; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The objectives of the study were: (1) to describe the application of Quick on the Draw model to improve expository writing skills; (2) to improve expository writing skills through the application of Quick on the Draw model; (3) to describe the obstacle and solution in implementing the Quick on the Draw model to improve expository writing skills. This collaborative classroom action research was conducted in three cycles. The subjects were the teacher and students of fifth grade of SDN 2 Karangpoh. The data were qualitative and quantitative data. Data collection techniques used observation, interviews, and tests. The data validity used triangulation of techniques and triangulation of sources. The data analysis included data reduction, data presentation, and conclusions drawing. The results showed that: (1) the steps of the Quick on the Draw model were: (a) delivering learning objectives, (b) preparing question cards, (c) creating group formation and learning material, (d) delivering rules of game, (e) having problem solving, (f) delivering results of discussion, (g) giving rewards, and (h) reviewing exam questions; (2) the application of the Quick on the Draw model improved expository writing skills; (3) the obstacle was the students focused on answering questions quickly but did not pay attention to the accuracy of the answers. The solution was the teacher guided the students to answer questions quickly and accurately.